Posisi dan Lama Duduk saat Bekerja dalam Menimbulkan Low Back Pain - Hartanto Hartanto; Budiman Hartono; Theodora Margaret (Fakultas Kedokteran dan Ilmu Kesehatan Ukrida, 2022)
Low back pain (LBP) is a pain sensation in the L1-S1 region that can radiate to the legs and feet. Position and long time sitting while working are one of the factors that cause LBP. The purpose of this study was to determine the position and long time sitting while working in causing LBP. The method used in the literature study was done by searching in the research journal databases, namely Google Scholar and Pubmed. The results obtained 11 articles that meet the inclusion and exclusion criteria. Sitting upright and hunched over increase complaints of LBP, because it affects the amount of pressure exerted on the spine. This pressure will cause microtrauma accompanied by inflammation, causing LBP. Sitting duration that more than 4 hours is sufficient to cause LBP and the risk of LBP increases when sitting for a longer time, ie 6–9 hours and >9 hours. Sitting for long time will cause the muscles to become tired, reducing muscle support to the spine. This causes the pressure on the ligaments and intervertebral discs to increase. In this literature study also found other factors that can cause LBP, namely: age, chair back, working period and stretching.